Potret Krisis Perusahaan First Travel Dalam Kacamata Manajemen Public Relations - Ascharisa Mettasatya Afrilia (JURNAL ILMU SOSIAL, 2017)
The corporate crisis is still considered a scary specter. Not a few companies are desperately avoiding a crisis without them realizing that could happen to anyone and anytime. Crisis can not absorb the feathers that will come to the company which one with which management system. Even companies that already have a big name, can still be hit by the crisis. Moreover, some preventive measures to cure the crisis, is also very important to enter the fall of the company to avoid bankruptcy. At this stage the role of Public Relations holds a very important position. Public Relations talks about strategic functions that are expected to position itself as a golden stone both from internal and external companies. The ideal spirit, crisis management of a company that made the public Public Relations is expected to be able to muffle and cure the crisis as bad as any condition that befall. The writing of this article aims to find out how the management of the company "First Travel" in the face of corporate crises by using descriptive qualitative analysis method found that "First Travel" should provide a role to Public Relations specifically because the crisis can not be handled quickly and easily.